It All Depends on the Dose Poisons and Medicines in European History - Grell, Ole Peter; Cunningham, Andrew; Arrizabalaga, Jon (Taylor & Francis, 2018)
This is the first volume to take a broad historical sweep of the close relation between medicines and poisons in the Western tradition, and their interconnectedness. They are like two ends of a spectrum, for the same natural material can be medicine or poison, depending on the dose, and poisons can be transformed into medicines, while medicines can turn out to be poisons. The book looks at important moments in the history of the relationship between poisons and medicines in European history, from Roman times, with the Greek physician Galen, through the Renaissance and the maverick physician Paracelsus, to the present, when poisons are actively being turned into beneficial medicines.